Using herbs and plant extracts to reduce the microbial load in meat and extend its shelf life - Asaad Majeed Alfatlawi, Mustafa; Mohanad Abbood Alhamid, Mohanad Abbood Alhamid; Sharaf Ali Hadi Al-Shaikh, Sharaf Ali Hadi Al-Shaikh; Ameer Salem Al-Esawi, Ameer Salem Al-Esawi (University of Thi-Qar Journal of agricultural research, 2025)
Herbs and plant extracts are in important part of preserving meat for a longer period, as they contain active compounds that have antibacterial properties that cause meat spoilage. They play an important role in improving the safety and quality of meat and reducing the harmful effects of microbial agents. Some herbs such as propolis, green tea, thyme, rosemary, basil, turmeric, and green tea contain active compounds such as phenols and flavonoids that contribute to reducing meat spoilage and extending its shelf life by combining them with polymers such as gelatin and chitosan in addition to improving sensory properties.